Public Expenditure and Financial Accountability Assessment : Federal Democratic Republic of Ethiopia (The City of Addis Ababa) - World Bank (World Bank, Washington, DC, 2020)
On August 6, 2018, development partners (DPs) received an official request from the Ministry of Finance (MoF) to conduct public expenditure and financial accountability (PEFA) assessments for the federal government and selected regional governments and the city of Addis Ababa. The objective of the PEFA assessments is to review the current performance of the PFM systems, processes, and institutions of the city of Addis Ababa using the new 2016 PEFA framework and the 2016 supplementary guidelines on subnational government (SNG) assessments and to track progress using the 2011 PEFA framework since the last PEFA assessment, which was in 2015. The assessments are aimed at assisting the government in identifying PFM weaknesses that may inhibit effective delivery of services to its citizens and the realization of its development objectives in general. Furthermore, the findings of the PEFA assessments will assist the government in refining the PFM Strategy that it has already developed and provide the basis for a coherent PFM reform program that can be supported by DPs, as well as through the government’s own initiatives.